Probabilistic interval stability assessment for structures with mixed uncertainty. (January 2016) - Wu, Di; Gao, Wei; Song, Chongmin; Tangaramvong, Sawekchai
Highlights: Structural stability assessment with random and interval variables is investigated. Proposed method calculates statistical characteristics of bounds of buckling loads. Correlated random variables can be considered and interval dependency is eliminated. PDFs and CDFs of bounds of structural buckling load are visualized. Statistical features of bounds are same as bounds of statistical features. Abstract: A new hybrid probabilistic and interval computational scheme is proposed to robustly assess the stability of engineering structures involving mixture of random and interval variables. Such hybrid approach possesses noticeable flexibility by directly implementing primitive information on uncertain system parameters, thus the validity of the structural safety assessment against uncertainties can be improved. By implementing the different types of uncertainties, the presented approach is able to separately investigate the effects of random and interval variables acting upon the overall structural stability. A unified interval stochastic sampling (UISS) approach is proposed to calculate the statistical characteristics (i.e., mean and standard deviation) of the lower and upper bounds of the linear bifurcation buckling load of engineering structure involving hybrid uncertain system parameters. Consequently, the stability profile of engineering structure against various uncertainties can be parametrically established, such that the bounds on the maximum structural buckling load at any particular percentile of probability can be effectively determined. Both academic and practically motivated engineering structures have been thoroughly investigated by rigorously establishing the corresponding structural stability profiles, so the applicability and accuracy of the proposed method can be critically justified.